1996
DOI: 10.1017/s0022112096002303
|View full text |Cite
|
Sign up to set email alerts
|

Low Reynolds number fully developed two-dimensional turbulent channel flow with system rotation

Abstract: Theoretical and experimental studies have been performed on fully developed twodimensional turbulent channel flows in the low Reynolds number range that are subjected to system rotation. The turbulence is affected by the Coriolis force and the low Reynolds number simultaneously. Using dimensional analysis, the relevant parameters of this flow are found to be Reynolds number Re* = u*D/v (u* is the friction velocity, D the channel half-width) and Ωv/u2* (Ω is the angular velocity of the channel) for the inner re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 18 publications
5
46
0
1
Order By: Relevance
“…has also been used in industrial fluid dynamics, but then sometimes with the bulk velocity U b replaced by the friction velocity [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…has also been used in industrial fluid dynamics, but then sometimes with the bulk velocity U b replaced by the friction velocity [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the asymmetric distributions of the mean flow and Reynolds stresses about the central line of the rotating channel are observed [3][4][5][6][7][8]. Meanwhile, the large-scale roll cells are generated due to the Taylor-Görtler instability and shift towards the pressure wall as the rotation rate increases [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Although some experimental and numerical investigations have been performed on rotating channel flows, most of them are mainly limited to the turbulence statistics, the near-wall structures, and the dynamic process related to the turbulence energy subject to system rotation without heat transfer [3][4][5][6][7][8]. Understanding the effects of system rotation on turbulent heat transfer in the rotating channel flow is a fundamental issue in turbulence modelling because any model aimed at predicting the thermal statistics in rotating turbulence should reproduce the essential features of this canonical situation.…”
Section: Introductionmentioning
confidence: 99%
“…The Among the studies of turbulent channel flows subjected to these three types of system rotations, the spanwise rotating turbulent channel flows have been studied extensively through experiments [23,24] and numerical simulations [14,[25][26][27][28][29][30][31][32][33][34][35][36][37]. It is reported that as the rotation number increases, turbulence is gradually enhanced on the pressure side and reduced on the suction side, further resulting in asymmetric distributions in the mean flow and Reynolds stresses [14,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. At the same time, large-scale roll cells come forth as a result of the Taylor-Görtler (T-G) instability [14,23,25,35].…”
Section: Motivationmentioning
confidence: 99%